2022
DOI: 10.1177/09564624221135294
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus retinitis in hospitalized people living with HIV in the late antiretroviral therapy era in São Paulo, Brazil

Abstract: Background There is scarce information on AIDS-related cytomegalovirus (CMV) retinitis in middle-income countries. The objectives of this study were to identify the prevalence of active CMV retinitis in severely immunosuppressed people living with HIV (PLWHIV) and to describe its main features. Methods This retrospective cohort study was carried out at a tertiary center in São Paulo, Brazil. We included hospitalized adults PLWHIV with CD4 count ≤100 cells/μL, ≥ one quantitation of CMV DNA in plasma, and indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
0
1
Order By: Relevance
“…Similar findings were observed in a prior study of CMV retinitis. 18 However, high values of quantitative detection of CMV-DNA in plasma (>50 000 IU/mL) were observed in the 2 patients of the present study with concomitant digestive system and neurological CMV-EOD, in CMV encephalitis cases, 27 and in CMV polyradiculopathy cases (J.E Vidal, personal communication). Therefore, it is possible that there is some relationship between the value of quantitative detection of CMV-DNA and the different clinical forms of CMV-EOD, particularly the neurological manifestations.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Similar findings were observed in a prior study of CMV retinitis. 18 However, high values of quantitative detection of CMV-DNA in plasma (>50 000 IU/mL) were observed in the 2 patients of the present study with concomitant digestive system and neurological CMV-EOD, in CMV encephalitis cases, 27 and in CMV polyradiculopathy cases (J.E Vidal, personal communication). Therefore, it is possible that there is some relationship between the value of quantitative detection of CMV-DNA and the different clinical forms of CMV-EOD, particularly the neurological manifestations.…”
Section: Discussioncontrasting
confidence: 44%
“…16,17 In the cART era, a recent prospective observational study of severely immunosuppressed cART-naive PLWHA reported that 12% of them had CMV-EOD; only one-third of them had retinitis, while two-thirds presented with histologically confirmed gastrointestinal illness. 5 In this line, a prior study carried-out in our hospital identified CMV retinitis in 1.7% of PLWHA with advanced immunosuppression, 18 less than a half of the percentage identified with digestive system CMV-EOD reported in the present study. These results confirm the epidemiological changes in the clinical profile of CMV-EOD in the cART era.…”
Section: Discussionsupporting
confidence: 43%